Participatory Historical Research with People with Learning Disabilities - Barden, Owen (OUP, 2026)
This entry introduces the subfield of participatory historical research with people with learning disabilities. This subfield is small, in terms of the numbers of researchers working within it. Yet is notable for its creativity, compassionate approach to research and commitment to social justice and the activist aims of disability studies and the disability rights movement. The entry begins by setting out the reasons participatory historical research with people with learning disabilities may be considered a form of social justice praxis, and introducing some of the practical and ethical issues it raises. The entry then traces the evolution of participatory historical research from its origins in the 1970s to the present day. Its origins in the disability rights movement underpin the philosophy of kind of research, which are explored in some depth. This exploration leads in turn to a a detailed consideration of the ethics of participatory approaches to historical research with people with learning disabilities. Some current research methods and approaches are outlined, before some considerations for future research are offered. The entry concludes by suggestion that the characteristics of creativity, compassion and commitment to social justice could potentially be harnessed to further advance and extend the subfield, reaching wider and more diverse audiences than it does currently.
Oxford Research Encyclopedia of Disability Studies
PUBLISHED
New York
Keywords: Participatory research; history; research methods; research ethics; intellectual disability; learning disability; research philosophy; activism; Digital Humanities; Identities in Transformation; Inclusive Society; Disability Inclusion; INTELLECTUAL DISABILITY; Inclusive research; LEARNING DISABILITY; Participatory Research Methods; archival research; Intellectual Disability; Attitudes; Advocacy and political participation; Deaf/Deafness; History; Social exclusion; Social participation